A Narrative Review about Nutritional Management and Prevention of Oral Mucositis in Haematology and Oncology Cancer Patients Undergoing Antineoplastic Treatments - Balma García-Gozalbo (MDPI AG, 2021)
Cancer is a prevalent disease worldwide, and treatments such as radiotherapy and chemotherapy sometimes lead to adverse events. Oral mucositis is one of the most disabling adverse events, and clinical guidelines do not take into account nutritional interventions. The primary endpoint was to gather the evidence about the efficacy of nutritional interventions in the prevention and/or treatment of antineoplastic-induced oral mucositis in oncological patients. A bibliographic review was carried out in the PubMed data base by combining MeSH terms with Boolean operators. Articles were selected based on inclusion and exclusion criteria; 50 final articles were found. Although further evidence is needed, glutamine, honey, and vitamins appear to be good therapeutic options. The rest of the compounds presented controversial or insufficient results, making it difficult to draw conclusions over their utilization as prevention or treatment options. Little evidence is reported about oral mucositis nutritional interventions in spite of them being attainable and affordable compounds. Scarce evidence is shown in paediatric patients compared with adults. Developing higher quality studies and combinations with the compounds researched is necessary for creating a stronger body of evidence.